Serial Music, Serial Aesthetics: Compositional Theory in Post-War Europe - Grant, M. J. (Cambridge Cambridge University Press, 2005)
Serial music was one of the most important aesthetic movements to emerge in post-war Europe, but its uncompromising music and modernist aesthetic has often been misunderstood. This book focuses on the controversial journal die Reihe, whose major contributors included Stockhausen, Eimert, Pousseur, Dieter Schnebel and G. M. Koenig, and discusses it in connection with many lesser-known sources in German musicology. It traces serialism's
Keywords: Stockhausen, Karlheinz -- 1928-2007; Eimert, Herbert -- 1897-1972; Pousseur, Henri -- 1929-2009; Schnebel, Dieter -- 1930-2018; Koenig, Gottfried Michael -- 1926-2021; 20th Century (1901-2000); Music history; Music theory; Avant-garde